Polyethylenimine-functionalized magnetic amorphous carbon fabricated from oil palm leaves as a novel adsorbent for Hg(II) from aqueous solutions - Mona El-Sayed Eid (Egyptian Journal of Petroleum)
PEI (polyethylenimine) functionalized magnetic amorphous carbon thin film nano composite (Fe3O4-PEI-ACTF NC), was successfully synthesized and characterized by High Resolution Transmission Electron Microscope (HR-TEM), X-ray diffraction (XRD), Fourier-transform infrared spectrometer (FTIR), and Thermo gravimetric analysis (TGA). The synthesized nano composite Fe3O4-PEI-ACTF was developed as a highly efficient adsorbent for Hg(II) from aqueous samples. Effect of pH, contact time, adsorbent dose, initial concentration and temperature were investigated and optimized through batch adsorption technique. Besides, good magnetic performance of Fe3O4-PEI-ACTF NC makes it easily recovered from water with magnetic separation at low magnetic field. The adsorption kinetic data described well with the pseudo-second-order model and the equilibrium data fitted well to Langmuir isotherm model. The maximum adsorption capacity was 714 µg/g of Hg(II). Thermodynamic studies (ΔG° < 0, ΔH° > 0, ΔS° > 0) implied an endothermic and spontaneous adsorption process in nature. Furthermore, the excellent reproducibility indicated that Fe3O4-PEI-ACTF NC has a promising application for removing heavy metals from aqueous environments due to high adsorption capacity and easily and quick separation. Keywords: Poly(ethyleneimine), Magnetic amorphous carbon, Hg(II) adsorption, Isotherm, Kinetics, Thermodynamics